Modification of Immediate Postplacenta CuT-380A IUD Insertion Using Ring Forceps and Standard Inserter: Twelve Months Follow-up - Tjahjanto, Hary; Hadiningrat, Wijoyo (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To evaluate the outcome of CuT-380A IUD postplacental insertion in vaginal delivery using new modification insertion technique. Method: We carried out a prospective cohort study of postplacental IUD insertion by means of ’push and push’ technique, using ring forceps and standard inserter (inserter tube and plunger rod). We included women who underwent vaginal delivery from 1st June 2009 until 31st March 2011 and had postplacental IUD insertion. Followup was conducted for 12 months, including history, physical examination, ultrasound and questionnaires during evaluation, through home visits and by phone. The first monitoring is before 6 weeks after delivery, the second monitoring was after 6 weeks up to 3 months, the third is after 3 months up to 6 months, the fourth is after 6 months up to 12 months, the fifth is after 12 months up to 24 months and the sixth is after 24 months up to 32 months after insertion. Result: On the second monitoring, 2 acceptors experienced expulsion. At the third monitoring period, one acceptor requested for IUD removal. At 9 months up to 12 months post-insertion, one expulsion was encountered, and one acceptor requested removal of device. At ≥12 months there was one acceptor who had IUD removal. We did not find any report of unintended pregnancy or perforation. Conclusion: Immediate post-placental insertion of CuT-380A IUD after vaginal delivery using ’push and push’ technique is safe and effective. The pregnancy rate at typical use is 0%, continuation rate is 94.1% and low expulsion rate (2.86%). Loss of follow up was 5.6% and no perforation was reported. Keywords: continuation rate, immediate post-placental IUD insertion, ’push and push’ technique, typical use, vaginal delivery